2022
DOI: 10.3389/fendo.2022.846154
|View full text |Cite
|
Sign up to set email alerts
|

Super-Enhancer-Associated Long Non-Coding RNA LINC01485 Promotes Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells by Regulating MiR-619-5p/RUNX2 Axis

Abstract: ObjectiveTo investigate the mechanisms of super-enhancer-associated LINC01485/miR-619-5p/RUNX2 signaling axis involvement in osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs).MethodsOsteogenic differentiation of hBMSCs was induced in vitro. The expression levels of LINC01485 and miR-619-5p during osteogenesis were measured using quantitative real-time polymerase chain reaction (qRT-PCR). Osteogenic differentiation was examined by qRT-PCR, western blot, alkaline phosphatase (ALP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Gu et al showed that LINC01485 could act as a ceRNA for miR-619-5p to affect RUNX2 expression and thus promote osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). The LINC01485/miR-619-5p/RUNX2 axis may be a new target in the field of bone tissue engineering (Gu et al, 2022). Ma et al also found that CIRC-FAT1 gene downregulation suppressed colorectal carcinogenesis by sponging miR-619-5p to inhibit FOSL2 expression, providing a potential pathway for colorectal cancer treatment (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al showed that LINC01485 could act as a ceRNA for miR-619-5p to affect RUNX2 expression and thus promote osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). The LINC01485/miR-619-5p/RUNX2 axis may be a new target in the field of bone tissue engineering (Gu et al, 2022). Ma et al also found that CIRC-FAT1 gene downregulation suppressed colorectal carcinogenesis by sponging miR-619-5p to inhibit FOSL2 expression, providing a potential pathway for colorectal cancer treatment (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%